TEKNIK MENINGKATAN KETERAMPILAN MENULIS DESKRIPSI PADA PEMBELAJARAN BAHASA INGGRIS MELALUI MEDIA GAMBAR PADA MAHASISWA PGSD KELAS 2A12 UNIVERSITAS QUALITY TAHUN AKADEMIK 2021/2022 - hasni suciawati; Gemala widiyarti; siti rakiyah (JURNAL CURERE, 2022)
The purpose of this research is to improve the writing ability of Quality university students, especially class 2A12 by using English. In improving writing skills, researchers used pictures as media to stimulate their abilities. From the results of observations made for some time, students' writing skills in English were very lacking. This happened because of the lack of stimulus used during the teaching and learning process, causing them to become less enthusiastic when given English assignments, especially writing assignments